The Influence of Brand Image, Price Perception, and Location on Purchasing Decisions - Pratiwi, Fuji (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Increasingly competitive competition, Kopi Kenangan cafes must innovate to keep up with the times. In the case of Bablue clothing & distro wajo, the decisions made by customers regarding purchases can affect the company's profits, so it is very important for business. This study aims to discuss the impact on brand image (X1), price perception (X2), and location (X3) as intervening variables on purchasing decisions (Y) at Bablue clothing & distro wajo. This study uses anti-survey arguments. The accidental sampling method was used to collect (n=100) individuals who had purchased Bablue clothing & distro wajo. Primary data collected directly from the respondents is used to analyze multiple regression analysis. Based on research findings, purchasing decisions on Bablue clothing & distro wajo are influenced by Brand Image. It is underlined that the perception of price and location has an impact on purchasing decisions.